DESIGNING ARABIC LANGUAGE LEARNING GAMES: CHALLENGES AND OPPORTUNITIES IN THE DIGITAL ERA - Khoiriyah Khoiriyah; Choi Seojin; Ida Rasmussen (Journal International of Lingua and Technology, 2026)
Arabic language learning faces persistent pedagogical challenges, particularly in maintaining learner engagement and addressing linguistic complexity in the context of rapid digital transformation. The increasing integration of digital technologies in education has positioned game-based learning as a promising approach to enhance motivation, interaction, and learner autonomy. However, the design of Arabic language learning games presents unique challenges related to linguistic accuracy, cultural representation, and pedagogical alignment, while simultaneously offering significant opportunities for innovation in the digital era. This study aims to examine the challenges and opportunities involved in designing Arabic language learning games and to identify key principles that support effective and meaningful learning. The research employed a qualitative-dominant mixed-methods design, involving questionnaires administered to Arabic language learners, semi-structured interviews with educators and game developers, and a focused case study of an Arabic learning game implementation. The findings reveal that digital games significantly enhance learner engagement and motivation, yet inconsistencies remain in linguistic depth and cultural authenticity due to design constraints and limited interdisciplinary collaboration. The study concludes that Arabic language learning games can function as effective instructional tools when pedagogical rigor, linguistic integrity, and engaging game mechanics are carefully balanced. These results highlight the importance of theory-informed and collaborative design approaches to optimize the educational potential of digital games in Arabic language learning.